The Effect of Micro Teaching Courses and Introduction to School Field on Student Teaching Readiness of the Faculty of Teacher Training and Education, University of Riau - Sri Annisa Chaniago; Caska Caska (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study aims to determine (1) the effect of the Micro Teaching Course on the Readiness to Teach FKIP University of Riau students. (2) the effect of Introduction to Schooling Fields on Teaching Readiness of FKIP University of Riau Students. (3) and the influence of Micro Teaching Subjects and Introduction to Schooling Fields on the Readiness to Teach FKIP University of Riau Students. The background of this research is that students' readiness to become teachers is still low. This research is included in the quantitative research. The population in this study were 1,066 FKIP University of Riau students class of 2018 with a research sample of 91 students. Sampling technique with proportional random sampling. Data collection techniques used are documentation and questionnaires. The classic assumption test includes the normality test, linearity test and multicollinearity test. Data analysis technique with multiple linear regression.